6-gingerol ameliorates gentamicin induced renal cortex oxidative stress and apoptosis in adult male albino rats. Issue 3 (June 2016) - Hegazy, Ahmed M.S.; Mosaed, Mohammed M.; Elshafey, Saad H.; Bayomy, Naglaa A.
Abstract: Ginger or Zingiber officinale which is used in traditional medicine has been found to possess antioxidant effect that can control the generation of free radicals. Free radicals are the causes of renal cell degeneration that leads to renal failure in case of gentamicin induced toxicity. This study was done to evaluate the possible protective effects of 6-gingerol as natural antioxidant on gentamicin-induced renal cortical oxidative stress and apoptosis in adult male albino rats. Forty adult male albino rats were used in this study and were randomly divided into four groups, control group; 6-gingerol treated group; gentamicin treated group and protected group (given simultaneous 6-gingerol and gentamicin). At the end of the study, blood samples were drawn for biochemical study. Kidney sections were processed for histological, and immunohistochemical examination for caspase-3 to detect apoptosis and anti heat shock protein 47 (HSP47) to detect oxidative damage. Gentamicin treated rats revealed a highly significant increase in renal function tests, tubular dilatation with marked vacuolar degeneration and desquamation of cells, interstitial hemorrhage and cellular infiltration. Immunohistochemically, gentamicin treated rats showed a strong positive immunoreaction for caspase-3 and anti heat shock protein 47 (HSP47). Protected rats showed more or less normal biochemical, histological, and immunohistochemical pictures. In conclusion, co-administration of 6-gingerol during gentamicin 'therapy' has a significant reno-protective effect in a rat model of gentamicin-induced renal damage. It is recommended that administration of ginger with gentamicin might be beneficial in men who receive gentamicin to treat infections.